Oxygenation decreases elastin secretion from rat ductus arteriosus smooth muscle cells*. Issue 4 (August 2015) - Kawakami, Shoji; Minamisawa, Susumu
Abstract Background The ductus arteriosus (DA), a fetal arterial connection between the main pulmonary artery and the descending aorta, normally closes immediately after birth. The oxygen concentration in the blood rises after birth, and in the DA this increase in oxygen concentration causes functional closure, which is induced by smooth muscle contraction. Previous studies have demonstrated that hypoxia and/or oxygenation affect vascular remodeling of various vessels. Therefore, we hypothesized that the rise in oxygen concentration would affect the vascular structure of the DA due to production of proteins secreted from DA smooth muscle cells (SMC). Methods and Results Liquid chromatography–tandem mass spectrometry was used to comprehensively investigate the secreted proteins in the supernatant of rat DA SMC harvested under hypoxic conditions (1% oxygen) or under normoxic conditions (21% oxygen). We found that the rise in oxygen concentration reduced the secretion of elastin from DA SMC. On reverse transcription–polymerase chain reaction, the expression of elastin mRNA was not significantly changed in DA SMC from hypoxic to normoxic conditions. Conclusions Given that elastin forms internal elastic lamina and elastic fibers in the vascular muscle layers, and that a rise in oxygen concentration reduced the secretion of elastin, this suggests that the rise in blood oxygen concentration after birth reduces the secretion of elastin, and therefore may play a role in DA structural remodeling after birth.